2019
DOI: 10.2174/2212796812666180507130017
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated Resistance against Plant Parasitic Nematodes of Wheat Plants Obtained in Vitro Using Bioregulators of Microbiological Origin

Abstract: Background: Plant parasitic nematodes are dangerous pests that damage various agricultural crops and decrease their productivity. Objective: The resistance of new lines of wheat (Triticum aestivum L.) plants obtained under in vitro conditions on MS media containing microbial bioregulators to plant parasitic nematodes was studied under in vitro and greenhouse conditions. Methods: Here we conducted physiological and molecular-genetic studies of resistance of wheat plants to nematodes. Results: In vitro ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
0
12
0
4
Order By: Relevance
“…Experimental evidence suggests that streptomycete-derived MBs stimulate growth and viability of crops, as has been recently demonstrated during in vitro, in vivo and greenhouse experiments on wheat [52,53,64], cucumbers [56], rapeseed [59], and Chinese cabbage [57]. Thus, we replace a constant growth rate of uninfected plants by a growing saturated function of the amount of applied MBs…”
Section: Model Derivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental evidence suggests that streptomycete-derived MBs stimulate growth and viability of crops, as has been recently demonstrated during in vitro, in vivo and greenhouse experiments on wheat [52,53,64], cucumbers [56], rapeseed [59], and Chinese cabbage [57]. Thus, we replace a constant growth rate of uninfected plants by a growing saturated function of the amount of applied MBs…”
Section: Model Derivationmentioning
confidence: 99%
“…with r (0) = r 0 and r (∞) = r 0 /s. Molecular genetic analyses show that MBs trigger a significant increase in the within-plant synthesis of si/miRNA homologous with plant genes associated with proteins that are important for a successful infection, as well as with viral genes, whose expression is needed for viral replication in plants [19,53,55,56,58,59]. To model this effect, we take the rate of disease transmission from infected vectors to plants in the form of a decreasing function of the amount of applied MBs as follows,…”
Section: Model Derivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Products of different streptomycetes have recently been shown provide effective nematicidal action (Ruanpanun et al, 2010; Rashad et al, 2015; Kaur et al, 2016). Recent work has shown that metabolites produced by some of the streptomycetes have a significant positive effect on plant performance through improved growth and development, and they also yield protection against nematode through stimulating production in plant cells of appropriate si/miRNA (Jailani and Mukherjee, 2017; Tsygankova et al, 2019). More specifically, metabolites and cell culture supernatant of soil streptomycetes S. avermitilis (Biliavska et al, 2012; Iutynska, 2012), S. netropsis (Biliavska et al, 2016a), and S. violaceus (Biliavska et al, 2016b) have been shown to possess strong antagonistic activity against various phytopathogenic micromycetes and bacteria (Iutynska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%